Informing Mathematics Teachers' Reflective Practice with Student Surveys on Affective Domain - McLaurin, Bruce (Université d'Ottawa / University of Ottawa, 2024)
This thesis examines the potential of a change analysis of student beliefs and attitudes about mathematics to inform teachers' reflective practice and provide the basis for modifying classroom practice. The author and two colleagues were involved in Math4theNines, a collaborative inquiry project for Ontario Grade 9 Mathematics. As part of that project, they developed an online survey to track the impact of their classroom practice on how students felt about mathematics and how students felt about themselves as learners of mathematics. The teachers reported that the before-and-after course survey and the accompanying change analysis that indicated any shifts in their students' attitudes and beliefs toward mathematics provided some unique and revealing perspectives on their practice. This study is a retrospective of that experience and an attempt to reproduce the results with three volunteer teachers. Although the results were mixed, there is some evidence to suggest that this approach has the potential to enhance teachers' focus on the new social-emotional strand in Ontario Grades 1 to 9 mathematics which presently is neither evaluated nor reported on. There is also potential to inform teachers in their efforts to develop the positive attitudes that have been shown to improve academic achievement and encourage entry into STEM fields.
Keywords: affective domain; secondary mathematics; self-reflection; student surveys